OPTIMIZATION OF BIOETHANOL PRODUCTION BY SACCHAROMYCES CEREVISIAE MICROENCAPSULATED ON ALGINATE-DELIGNIFIED CELLULOSE MATERIAL - SA ALTING; ZHONG ZHAOPING (International Journal of Pharma and Bio Sciences, 2015)
The aim of this research was to enhance bioethanol production via immobilization and microencapsulation of Saccharomyces cerevisiae CICC 1001 into delignified cellulosic material (DCM), prepared from sawdust and Na alginate. It has been demonstrated that microencapsulation process using Alginate: DCM ratio of (1:1.5) and alginate solution of 2.5% by wt, attained the highest microencapsulation efficiency. In addition, microwave alkali pretreated sugarcane bagasse was used as a substrate for second-generation ethanol production. A maximum ethanol yield of 0.37g/g theoretical yield was obtained after 96h of incubation from DCM-Alginate microcapsule, which was 42.3% higher than that of alginate alone. The microcapsule was used up to nine cycles in order to study about its stability and the strength of yeast cell for ethanol production. Optimization of ethanol production was examined using the Box–Behnken design (BBD) of response surface methodology. The pH (4-5.5), fermentation time (24-72 h), and solid content loading (15-20%w/v) were tested to maximize bioethanol yield in the SSF process. The predicted optimum conditions were pH 4.5, 56.42h fermentation time, and 15.16%w/v solid content loading. Overall, this work will be meaningful in the conversion of lignocellulosic agro-waste to generate bioethanol.